2012
DOI: 10.1093/cid/cis757
|View full text |Cite
|
Sign up to set email alerts
|

Serological Response to Treatment of Syphilis According to Disease Stage and HIV Status

Abstract: The serological response to treatment was studied in 264 syphilis patients; it was influenced by syphilis stage but not by human immunodeficiency virus infection and reinfection. Some of the recommendations of current guidelines are critically discussed, and amendments are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 28 publications
8
64
1
6
Order By: Relevance
“…Reactive specimens are retested in 2-fold dilution series for quantitative results. Titers usually decline significantly after successful therapy and are dependent on the syphilis stage as well as on the presence of HIV coinfection (16)(17)(18). Romanowski et al reported that patients with high pretreatment titers had a greater rate of decline than those with lower titers but were less likely to revert to the negative condition (19).…”
Section: Serologic Testsmentioning
confidence: 99%
“…Reactive specimens are retested in 2-fold dilution series for quantitative results. Titers usually decline significantly after successful therapy and are dependent on the syphilis stage as well as on the presence of HIV coinfection (16)(17)(18). Romanowski et al reported that patients with high pretreatment titers had a greater rate of decline than those with lower titers but were less likely to revert to the negative condition (19).…”
Section: Serologic Testsmentioning
confidence: 99%
“…Although further study is required, it may be prudent to screen all individuals with a repeat syphilis diagnosis three to six monthly or, failing that, screen them six monthly with a more sensitive test such as an IgM test. A study from 1999 to 2008 in Zurich, Switzerland, found that an IgM enzymelinked immunosorbent assay was negative in considerably fewer cases of primary syphilis cases compared with the RPR test (4% vs 42%) [30].…”
Section: (V) Missed Signs Of Diseasementioning
confidence: 99%
“…The systematic review by Blank et al was focused on HIV coinfected population (19); however, the review by Clement et al, focused more broadly on syphilis with some discussion of HIV co-infection (20). Studies were conducted in Taiwan (37), the United States (38) and Europe (39)(40)(41). The participants in the studies were predominantly male.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The participants in the studies were predominantly male. In four studies, the intervention was one or three doses of BP-G (37,(39)(40)(41). A single study compared one dose of BP-G with two or more doses of BP-G (38) ( Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation